Wooden Domes History and Modern Times - Misztal, Barbara (Springer International Publishing, 2018)
This monograph presents a state-of-the-art analysis of eco-friendly and aesthetic structures in wooden dome construction. The author demonstrates that the further development of wooden structures depends on both supplementing the testing of wood as a heterogeneous material, as well as on further improvement of fibrous structures with visco-elastic properties. The target audience primarily comprises research experts and practitioners in the field of building materials who are interested in innovative architecture.